The development of professional competences using the interdisciplinary project approach with university students - Mònica González-Carrasco; Jesús Francés Ortega; Rodolfo de Castro Vila; Margarida Castañer Vivas; Joan San Molina; Joan Marti Bonmati (OmniaScience, 2016)
This work describes an experience conducted by a group of professors from different departments at the University of Girona (Catalonia, Spain) which arose from the need for interdisciplinary work in university classrooms in order to promote competences relevant to the professional sector. As part of this experience, students from different degree programs were challenged to work collaboratively and in an interdisciplinary manner on a project related to the management of a school cafeteria designed for a real educational center. The work promoted the development of competences that are otherwise difficult to attain through activities that lack an interdisciplinary approach, which are key in today's professional world, such as multi-professional teamwork. Based on this experience, the feasibility of students from different areas of study carrying out a final degree project (FDP) that meets real, contextualized needs and requires the contribution of knowledge from different disciplines is considered.